Genetics and evidence for balancing selection of a sex-linked colour polymorphism in a songbird - Kang-Wook Kim (Nature Portfolio, 2019)
Gouldian finches have a head colour polymorphism that is also associated with physiological and behavioural differentiation. Here, the authors map this colour polymorphism to a putative regulatory region for follistatin on the Z chromosome and suggest it is maintained by balancing selection.